2016
DOI: 10.1002/pssr.201600272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the firing temperature profile on light induced degradation of multicrystalline silicon

Abstract: Light‐ and elevated temperature‐induced degradation in multicrystalline silicon can reduce the efficiency of solar cells significantly. In this work, the influence of the firing process and its temperature profile on the degradation behaviour of neighbouring mc‐Si wafers is analysed. Five profiles with measured high peak temperatures ≥800 °C and varying heating and cooling ramps are examined. With spatially resolved and lifetime calibrated photoluminescence images, normalized defect concentrations N*t are calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 16 publications
3
55
0
Order By: Relevance
“…In particular, Eberle et al 27,28 observed that a fast ramp rate in RTA induces strong LeTID, while a slower ramp rate practically eliminates it-which is similar to the behaviour observed in this study. Furthermore, several other studies [29][30][31][32] have consistently reported that the magnitude of LeTID increases with peak firing temperature, with peak temperatures 650 C leading to little or no LeTID, while temperatures between 700 C and 950 C trigger degradation.…”
Section: à3supporting
confidence: 89%
“…In particular, Eberle et al 27,28 observed that a fast ramp rate in RTA induces strong LeTID, while a slower ramp rate practically eliminates it-which is similar to the behaviour observed in this study. Furthermore, several other studies [29][30][31][32] have consistently reported that the magnitude of LeTID increases with peak firing temperature, with peak temperatures 650 C leading to little or no LeTID, while temperatures between 700 C and 950 C trigger degradation.…”
Section: à3supporting
confidence: 89%
“…to above 10% rel. , depending on the wafer bulk and the solar cell processing [1][2][3][4][5][6][7][8]. LeTID formation is particularly sensitive to the peak temperature [3] and the cooling profile of the firing step [4].…”
Section: Introductionmentioning
confidence: 99%
“…, depending on the wafer bulk and the solar cell processing [1][2][3][4][5][6][7][8]. LeTID formation is particularly sensitive to the peak temperature [3] and the cooling profile of the firing step [4]. PERC cells that have been fired above 675°C [3] and cooled down rapidly show strong homogenous LeTID in the mc grains, with lower defect densities at the grain boundaries [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LeTID may result in over 10% relative efficiency loss in cells with dielectrically‐passivated rear side, which is a significant issue for the PV industry that is shifting towards passivated emitter and rear cells (PERC) . Hence, several PV research groups, academic institutions, and companies have recently investigated methods to mitigate the detrimental phenomenon, eg, via dark annealing, reduced peak temperature or ramp rates of fast firing, application of high‐intensity illumination at elevated temperature, or phosphorus diffusion gettering of LeTID‐causing impurities …”
Section: Introductionmentioning
confidence: 99%